2017
DOI: 10.3390/nano7120415
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Exchange Bias and Coercivity in Fe3O4–γ-Fe2O3 Core–Shell Nanoparticles of Fixed Core Diameter and Variable Shell Thicknesses

Abstract: We have carried out extensive measurements on novel Fe3O4–γ-Fe2O3 core–shell nanoparticles of nearly similar core diameter (8 nm) and of various shell thicknesses of 1 nm (sample S1), 3 nm (sample S2), and 5 nm (sample S3). The structure and morphology of the samples were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), and selected area electron diffraction (SAED). The direct current (DC) magnetic measurements were carried out using a superconducting quantum interference device (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
2
26
1
1
Order By: Relevance
“…Due to the broken exchange bonds [53] at the core/shell interface, the interface spins are suggested to be in disordered states. We suggest that (as shown in [37]) at the core/shell interface, spin-glass like structures [49,50] occur with amounts that increase with shell thickness. Hence, we attribute the increase of α B (increase of deviation from the original Bloch's law) with shell thickness to the increase of spin-glass structures as the shell thickness increases.…”
Section: Magnetic Propertiessupporting
confidence: 51%
See 2 more Smart Citations
“…Due to the broken exchange bonds [53] at the core/shell interface, the interface spins are suggested to be in disordered states. We suggest that (as shown in [37]) at the core/shell interface, spin-glass like structures [49,50] occur with amounts that increase with shell thickness. Hence, we attribute the increase of α B (increase of deviation from the original Bloch's law) with shell thickness to the increase of spin-glass structures as the shell thickness increases.…”
Section: Magnetic Propertiessupporting
confidence: 51%
“…Thus, to obtain larger/smaller shell thickness, we started with larger/smaller particles (longer/shorter reaction times) and allowed for longer/shorter diffusion times. By optimizing these two parameters we were able to determine the suitable initial particle size for each diffusion time such that we obtained a fixed core for each case [37]. We found that when the reaction time is 1 h and the diffusion time is 1 h the core diameter is 8 nm and the shell thickness is 1 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the hollow NCs show a size-dependent blue shift, strong visible-light and broad infrared absorption phenomenon [ 21 ]. The α-Fe 2 O 3 nanomaterials show ferromagnetic behavior and high coercivity in magnetic hysteresis measurements [ 22 , 23 ]. The rational design and synthesis of nanomaterials with different morphology have become an effective strategy to improve their optical, magnetic and electrochemical properties [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее перспективными для биомедицинских приложений являются МНЧ Fe 3 O 4 /γ-Fe 2 O 3 типа Я/О, состоящие из биологически совместимых компонентов, а именно магнетита (Fe 3 O 4 ) и маггемита (γ-Fe 2 O 3 ) [4,5]. Однако магнитные свойства, природа обменного смещения и другие эффекты в МНЧ типа Я/О полностью еще не поняты, хотя исследованиям таких МНЧ посвящено много публикаций (см., например, работы [1,4,6,7]…”
unclassified